Deconvoluting the Innocent vs. Non‐Innocent Behavior of N, N‐Diethylphenylazothioformamide Ligands with Copper Sources. Issue 47 (18th December 2017) - Johnson, Nicolas A.; Wolfe, Samuel R.; Kabir, Humayun; Andrade, Gabriel A.; Yap, Glenn P. A.; Heiden, Zachariah M.; Moberly, James G.; Roll, Mark F.; Waynant, Kristopher V.
Abstract : Redox‐active ligands lead to ambiguity in often clearly defined oxidation states of both the metal center and the ligand. The arylazothioformamide (ATF) ligand class represents a redox‐active ligand with three possible redox states (neutral, singly reduced, and doubly reduced). ATF–metal interactions result in strong colorimetric transitions allowing for the use of ATFs in metal detection and/or separations. While previous reports have discussed dissolution of zerovalent metals, the resulting oxidation states of coordination complexes have proved difficult to interpret through X‐ray crystallographic analysis alone. This report describes the X‐ray crystallographic analysis combined with computational modeling of the ATF ligand and metal complexes to deconvolute the metal and ligand oxidation state of ATF–metal complexes. Metal(ATF)2 complexes that originated from zerovalent metals were found to exist as dicationic metal centers containing two singly reduced ATF ligands. When employing Cu I salts instead of Cu 0 to generate ATF–copper complexes, the Cu I in the resulting complexes remained in its oxidation state, and the ATF ligand remained "innocent", existing in its neutral state. Although the use of CuX (X = Br or I) or [Cu(NCMe)4 ]Y (Y = BF4 or PF6 ) generated species of the type: [(ATF)Cu(µ‐X)]2 and [Cu(ATF)2 ]Y, respectively, the ATF ligand remained in its neutral state for each species type. Abstract : Experimental and computational investigation of reactions involving the redox‐active arylazothioformamide ligand with multiple Cu I sources is described. Cu I halides produce dimeric 1:1 coordination species, while non‐coordinating counterions (BF4 – and PF6 – ) gave 2:1 species. Computational comparisons of bond lengths and angles suggest that the Cu atom remains in the +1 oxidation state.